Pelatihan, Pengalaman Kerja, Kompetensi dan Motivasi Sebagai Faktor Penentu Terhadap Kinerja Tenaga Kesehatan - Ratih Indriane Septiani; Kartawan Kartawan; Yusuf Abdullah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to determine the effect of training, work experience, competence and motivation on performance. The study was conducted on mental health management employees at the Tasikmalaya Regency Regional Health Center. Sampling was carried out using census techniques, with a sample size of 97 samples, consisting of mental health management employees at the Tasikmalaya Regency Regional Health Center, which consists of 40 Community Health Centers. The research instrument used was a questionnaire with a Likert scale. The analysis technique used is path analysis using the SPSS application. The results of this research show that: 1) Training, work experience, competence, motivation and performance are in good condition. 2) Training, work experience and competence have a positive and significant effect on performance, motivation has a positive but not significant effect on performance. 3) Training, work experience, competency and motivation have a significant effect on the performance of mental health management health workers at the Tasikmalaya Regency Regional Health Center